(untitled) (Mongolian Journal of Geography and Geoecology, 2025)
Geoecological mapping plays a critical role in advancing sustainable land management by enabling the integration of geological, geomorphological, and ecological dynamics. This study elaborated a geoecological map by incorporating detailed geomorphological and ecological information using a knowledge-based mapping approach. The methodology combines rule-based logic, expert interpretation, and the integration of various spatial datasets. Geological relationships, including stratigraphic sequences, lithological associations, and fault structures were encoded within a rule-based framework to ensure spatial and conceptual coherence. Expert knowledge, we derived from pre-existing geological and geomorphological data and supported by conceptual models, guided manual digitization and semi-automated interpretation processes. Multi-source datasets, including satellite imagery, digital elevation models (DEMs), and seismological layers, were integrated using domain-specific reasoning strategies. Geoecological units were delineated by considering the combined cumulative effects of three primary driving forces: (1) endogenic factors, stemming from deep-seated geodynamic processes such as tectonics and seismic activity; (2) exogenic factors, related to surface processes such as weathering, erosion, and mass movement; and (3) technogenic factors, resulting from human-induced changes including land use alterations, infrastructure development, and resource exploitation. The final geoecological map offers a robust analytical framework for understanding landscape evolution, assessing environmental vulnerability, and supporting evidence-based decision-making in land-use planning and natural resource management.